"Bringing DNA into the Neighborhood" in San Francisco: A Personal Recollection. (March 2016) - Risse, Guenter B.
Based primarily on personal experiences, this article aims to illustrate the troublesome relationship between the University of California, San Francisco (UCSF), and its adjoining neighborhoods from the 1960s to the present. Like other University of California campuses, UCSF was not required to conform to local land uses and zoning laws. Only its periodic and mandatory Long Range Development Plans provided clues about future research initiatives and expansion plans. The story, punctuated by indifference to neighborhood concerns, depicts the protracted legal wrangling between a world-renowned medical institution and local civic organizations fearful of its impact on the environment, residential life, and real estate. The featured focus of these disputes centered around UCSF's hasty purchase in 1984 of a large facility located in the Laurel Heights neighborhood of San Francisco to alleviate crowding at the main campus on Parnassus Heights. Confusion, misunderstanding, and outright distrust concerning UCSF's planning for the new research location ensued. In fact, fear of potential chemical emissions and radioactive contamination prompted stiff local resistance. Eventually, after a decade of litigation, the protracted case forced UCSF to redefine and restrict its mission at Laurel Heights. The article argues that the Medical Center's subsequent leadership learned an important lesson from this costly lawsuit. In its subsequent efforts to expand locally, UCSF created mechanisms designed to prevent opposition and litigation by systematically engaging with San Francisco communities and their leaders. By the early twenty-first century, such partnerships and alliances paved the way for a successful institutional expansion, thus consolidating UCSF's role as a leader in biomedical research, teaching, and practice.